PERANCANGAN TEMPAT PENGOLAHAN SAMPAH TERPADU REFUSE DERIVED FUEL (TPST RDF) DI TPA REGIONAL BLANG BINTANG, KABUPATEN ACEH BESAR - Sina Fikri Pasaribu, Agus
The problem of waste management in Indonesia is the collect-transport-dispose paradigm still exists (Damanhuri, 2000). In this condition, Aceh Besar District and Banda Aceh City in 2042 are projected to generate waste 477,91 tons/day or 1.762,29 m3/day and 341,25 tons/day or 908,61 m3/day and ended up at the Blang BintangRegion Landfill. The results of the proximate analysis of the chemical characteristics of the waste showed the potential for conversion of waste to energy with the measurement of the calorific value up to 3217,582 kcal/kg. For this reason, in this paper, a waste processing facility is designed that can solve the waste problem in both regions by using the Waste to Energy concept. Through the Analytic Hierarchy Process (AHP) method and the Simple Additive Weighting (SAW) method, the technology for processing waste into alternative fuel is Refuse Derived Fuel (RDF) with the bio drying method of drying. By using a moderate scenario, gradually increasing the fulfillment of the JAKSTRANAS target until the design year 2042, it is estimated that the waste generation entering the processing area is 730,349 tons/day or 2.373,2 m3/day. The design of the Integrated Municipal Solid Waste Management Refuse-Derived Fuel at the Blang Bintang Region Landfillis estimated to be successful in producing RDF of 416,61 tons/day with moisture content 22% and size ?50 mm. The results of the RDF will be used by the cement factory PT. SBI as an alternative fuel in kiln combustion.